2021
DOI: 10.1038/s41598-020-79830-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin protects cancer cells from apoptosis by regulation of mitochondrial cardiolipin

Abstract: Cytoglobin is important in the progression of oral squamous cell carcinoma but the molecular and cellular basis remain to be elucidated. In the current study, we develop a new cell model to study the function of cytoglobin in oral squamous carcinoma and response to cisplatin. Transcriptomic profiling showed cytoglobin mediated changes in expression of genes related to stress response, redox metabolism, mitochondrial function, cell adhesion, and fatty acid metabolism. Cellular and biochemical studies show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 94 publications
2
8
1
Order By: Relevance
“…Yet, in G361-shCYGB cells, NRF2 and HO-1 levels were reduced by half, which could potentially have a large biological impact. This is in accordance with other studies that showed a downregulation of antioxidant enzymes or a dysregulation of the NRF2 pathway upon loss of CYGB [ 24 , [64] , [65] , [66] ].…”
Section: Discussionsupporting
confidence: 93%
“…Yet, in G361-shCYGB cells, NRF2 and HO-1 levels were reduced by half, which could potentially have a large biological impact. This is in accordance with other studies that showed a downregulation of antioxidant enzymes or a dysregulation of the NRF2 pathway upon loss of CYGB [ 24 , [64] , [65] , [66] ].…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, the knockdown of CYGB also affected NRF2 and HO-1 protein expression under basal conditions ( Figure S3 ). This is in accordance with previous studies [ 14 , 39 , 40 , 41 ] and is consistent with results obtained recently by our group [ 31 ]. Considering NRF2’s central role in heme biosynthesis, and taking into account CYGB as a heme-containing protein, cells possessing abundant endogenous CYGB levels constitutively induce NRF2 protein, and subsequently HO-1 [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, cardiolipin (CL) was shown to be necessary for NLRP3 inflammasome activation [ 72 ]. As CYGB can interact with and regulate the redox status of CL [ 41 , 73 ], CYGB could indirectly regulate pyroptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…This further places the model of ROS molecules, which “flood” the whole cell from a single location of ROS production in rather unrealistic light. Nevertheless, the model of ROS as “flooding” the cell is still popular in the scientific community, often referred to as “total cellular ROS levels” ( Wang et al, 2013 , 2019 ; Dinakar et al, 2016 ; Kim and Xue, 2020 ; Loth et al, 2020 ; Thorne et al, 2021 ), “intracellular ROS levels” ( Tepel et al, 2000 ; Bensaad et al, 2009 ; Choi et al, 2011 ; Lee et al, 2017 ; Wang et al, 2019 , 2021a ; Wei et al, 2019 ; Zaidieh et al, 2019 ; Zhang W. et al, 2019 ; Mendiola et al, 2020 ; Winitchaikul et al, 2021 ; Zhong et al, 2021 ) or simply “ROS levels” ( Chen et al, 2012 , 2021 ; Wei et al, 2019 ; Agarwal and Ganesh, 2020 ; Kim et al, 2021 ; Knight et al, 2021 ; Zeller et al, 2021 ) in many studies, mainly because of the usage of diffusible ROS probes, which suggest free diffusion of ROS through the cell without regard of the location of ROS production. Mutations, e.g., in cancer cells ( Schumacker, 2006 ; Liou and Storz, 2010 ; Reczek and Chandel, 2017 ; Zaidieh et al, 2019 ; Perillo et al, 2020 ), pathogenic invasion ( West et al, 2011a ; Abuaita et al, 2018 ; Gluschko et al, 2018 ; Roca et al, 2019 ) or metabolic disbalance ( Li et al, 2016 ; Mak et al, 2017 ; Peng et al, 2021 ) are prominent examples, in which the ROS production of the cell can enter an uncontrolled stage and quickly overcome the antioxidative defense system leading to rapidly increased ROS levels in nearly every compartment of the cell with often detrimental consequences.…”
Section: Ros Production: the Dose Makes The Poisonmentioning
confidence: 99%